Studies on osmotic dehydration of green pepper - SMITHA K. E; Dr. Santhi Mary Mathew (Guide) (Tavanur 2008 Department of Post-Harvest Technology and Agricultural Processing)
Studies on osmotic dehydration of green pepper
Studies on osmotic dehydration of green pepper